Impact of the selection of statistical climate data on the energy demand for air conditioning treatment - Kwiecień , Dariusz (Instal, 2020)
The energy demand for air treatment is essential for determining the energy efficiency of any designed ventilation and air conditioning system. They are normally determined on the basis of climatic data based on long-term measurements in the form of so-called Typical Meteorological Years. The choice of source of climatic data can cause significant differences in the calculation results. This was confirmed in calculations carried out on the basis of data obtained from two different sources. The article presents and discusses the results of calculations of energy demand for air treatment for several selected locations in Poland. The results obtained show that the choice of statistical climate data has the greatest impact on the calculated energy demand for air cooling and the relatively lowest on the energy demand for humidification.